Uji Kualitatif Kandungan Parasetamol pada Jamu Pegal Linu dengan Metode Kromatografi Lapis Tipis (KLT) - Azzahra, Intan Apriyola Ropi; Saraan, Sri Muftri Diani; Hilmi, Anisa Prima; Putra, Naufal Anugerah; Visca, Annisa Septania (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Herbal medicine for muscle and joint pain is a traditional medicine widely used by the public to help reduce muscle and joint pain. However, the potential addition of chemical drugs (BKO), such as paracetamol, is still a concern because it can pose health risks if consumed without supervision. This study aims to identify the presence of paracetamol in herbal medicine samples using the Thin Layer Chromatography (TLC) method. The research samples consisted of several herbal medicine preparations obtained from the market and were analyzed qualitatively by comparing the characteristics of sample spots to the paracetamol reference standard based on the retention factor (Rf) value and visualization under 254 nm UV light. The analysis results showed that the Rf value of the paracetamol standard in the test system used was within a certain range, while the analyzed herbal medicine samples did not show spots that were parallel to the reference standard. Based on these results, all tested samples were declared negative for the presence of paracetamol. This study shows that the TLC method can be used for the initial identification of the presence of paracetamol in herbal medicine samples in the scope of the qualitative testing conducted.